Modulating the Growth, Antioxidant Activity, and Immunoexpression of Proinflammatory Cytokines and Apoptotic Proteins in Broiler Chickens by Adding Dietary Spirulina platensis Phycocyanin - Anaam E. Omar; Hanan S. Al-Khalaifah; Ali Osman; Ahmed Gouda; Shimaa I. Shalaby; Elshimaa M. Roushdy; Samar A. Abdo; Sozan A. Ali; Aziza M. Hassan; Shimaa A. Amer (MDPI AG, 2022)
This study investigated the dietary effect of Spirulina platensis phycocyanin (SPC) on growth performance (body weight (BW), body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR)) at starter, grower, and finisher stages, intestinal histomorphology, serum biochemical parameters, inflammatory and antioxidant indices, and proinflammatory cytokines (tumor necrosis factor-α and caspase-3) immune expression in broiler chickens. In total, 250 one-day-old chicks (Ross 308 broiler) were randomly allotted to five experimental groups (5 replicates/group, 10 chicks/replicate) and fed basal diets supplemented with five levels of SPC (0, 0.25, 0.5, 0.75, and 1 g kg-1 diet) for 35 days. Compared with SPC0 treatment, different SPC levels increased the overall BW and BWG without affecting the total feed consumption. However, the FCR decreased linearly with an increase in supplementation level. The serum levels of total proteins, albumin, globulins, and growth hormone increased linearly by increasing levels of SPC supplementation. Further, SPC supplementation increased the thyroxin hormones without affecting serum glucose and leptin levels. Serum total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) values decreased in broilers fed SPC0.250 and SPC1 diets. Triglycerides (TG) decreased in SPC0.25-, SPC0.75-, and SPC1-treated groups. Though antioxidant enzyme activities (total antioxidant capacity, catalase, and superoxide dismutase) increased linearly and quadratically, malondialdehyde (MDA) decreased linearly by increasing the SPC level. There was no effect on serum proinflammatory cytokines IL1β levels. Immunolabelling index of caspase-3 and tumor necrosis factor-α (TNF-α) were downregulated by SPC supplementation. The intestinal histomorphology is represented by increased villus height, the villus height to crypt depth ratio, and numbers of goblet cells in different sections of the small intestine. In conclusion, SPC supplementation is beneficial in broiler chicken diets due to its growth-promoting, antioxidant, and anti-inflammatory properties.